Determine the Effect of Counseling on the Behavior and Motivation of CPA about Contraceptive Implants at Medan Sunggal Health Center in 2018 - Bangun, Adriana; Ginting, Daniel; Sembiring, Rinawati (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Family Planning is an effort to control the childbirth in order to realize a quality family. Implants are a means of contraception that the couples of productive age (CPA) are not interested in. Based on data obtained at Medan Sunggal Health Center, implant is the lowest after IUD. This is because there are still many CPA who are afraid to use implants because of their lack of knowledge. The Purpose of this study was to determine the effect of counseling on thee behavior and motivation of CPA about contraceptive implants at Medan Sunggal Health Center. The sampling technique was determined by Accidental Sampling method with 66 respondents. Research type was quasi-experiment with one group pretest posttest design. The results of research obtained by using T test were the value of knowledge, attitude and motivation (P value <0.001). It can be concluded that there is influence of counseling to behavior and motivation of CPA on contraceptive implants.